PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. MITRA ADIPERKASA, TBK - Rumondang Yeremia; Nuridin (Jurnal Manajemen Bisnis Krisnadwipayana, 2022)
To analyze the effect of compensation and work discipline on employee performance PT. Mitra Adiperkasa, Tbk. The research method uses descriptive analysis, the analysis model used is linear regression both simply and multiple. The study population was all employees of PT. Mitra Adiperkasa, Tbk, Fashion Division with 30 employees. The sampling technique of this research uses saturated nonprobability sampling which is the technique of determining the sample if all members of the population are used as samples. The findings of compensation and work discipline have a positive and significant effect on the performance of employees of PT. Mitra Adiperkasa, Tbk, both partially and simultaneous.